Heat-treatment-free die-casting aluminum alloy and preparation method thereof
By using Sb element metamorphism treatment and rotary degassing processes in heat-free die-cast aluminum alloys, the melt intake and elongation unstable caused by Sr element metamorphism is solved, and the internal structure of high strength and high elongation castings is achieved with a small and uniform effect without obvious holes and loose holes.
Patent Information
- Application Number
- CN202311425109.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-31
- Publication Date
- 2025-05-02
AI Technical Summary
The deterioration of Sr elements in existing heat-free die-cast aluminum alloys leads to melt suction, resulting in unstable elongation, and obvious holes and loose defects inside the castings, which is difficult to meet the requirements of high strength and high elongation.
By adding Sb elements instead of Sr elements, eutectic silicon is deteriorated, combined with the rotary degassing process, the hydrogen content in the alloy melt is controlled to ensure that the internal structure of the casting is small and uniform, and there are no obvious holes and loose holes.
The casting is achieved with high yield strength (greater than 120MPa) and high elongation (greater than 14%), avoiding the high hydrogen content caused by melt suction with high Sr content, and ensuring the internal quality and mechanical properties of the casting.
Smart Images

Figure CN119913402A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of die-casting aluminum alloys, and in particular relates to a heat-treatment-free die-casting aluminum alloy and a preparation method thereof. Background Art
[0002] The development of the modern automobile industry has promoted the demand for high-strength and toughness die-casting aluminum alloys. Since the 1990s, researchers at home and abroad have been committed to developing high-strength and toughness die-casting aluminum alloy materials based on high vacuum die-casting technology, and mainly Al-Si-Mg alloys (typical alloy composition AlSi10MnMg). This is because Mg and Si in Al-Si-Mg alloys can form Mg2Si. During heat treatment, Mg2Si can be dissolved into the matrix and then precipitated during aging, which plays a role in strengthening the alloy. At the same time, Si particles can be spheroidized and passivated during the solution process, thereby improving the plasticity of the alloy.
[0003] Traditional aluminum die-casting car body parts usually need heat treatment to meet high elongation performance. However, as the size of integrated castings becomes larger and larger, deformation is prone to occur during heat treatment, resulting in a decrease in yield rate. Therefore, heat-free materials will become the best choice in the implementation of integrated die-casting technology. The requirements for the as-cast tensile mechanical properties of large integrated thin-walled parts are: yield strength ≥120MPa, tensile strength ≥200MPa, and elongation ≥10%.
[0004] In view of the insufficient performance of existing die-cast aluminum alloys without heat treatment, a number of manufacturers or research institutions have disclosed some patents for die-cast aluminum alloys without heat treatment.
[0005] Chinese patent publication number CN115505795A discloses a heat-treatment-free aluminum alloy material, comprising the following components: Si, Fe, Cu, Mn, Mg, Zn, Ti, Sr, Zr, Cr, B, rare earth La+Y, Al and inevitable impurity elements, wherein the components are matched in percentage as follows: Si: 7.0-10.5%, Fe: 0.1-0.8%, Cu: 0.95-4.0%, Mn: 0.2-0.7%, Mg: 0.4-1.44%, Zn: 0.1-1.2%, Ti: 0.036-0.1%, Sr: 0.02-0.06%, Zr: 0.002-0.06%, Cr: 0≤Cr<0.008%, B: 0≤B<0.002%, rare earth La+Y: 0≤La+Y<0.2%, and the balance is Al and inevitable impurity elements. The advantages of this invention are: in terms of composition design, Si is controlled within the range of 7-10% hypoeutectic series, which can greatly improve the fluidity and filling capacity of the aluminum alloy. Through the synergistic effect of other elements, while ensuring a certain elongation, the yield strength is improved, the grain size of the die-cast structural parts is significantly refined, and a double refinement effect is achieved.
[0006] Chinese patent publication number CN115094281A discloses a heat-treatment-free and bake-strengthened die-cast aluminum-silicon alloy, a preparation method and a bake-strengthening method, wherein the mass percentage of each element in the die-cast aluminum alloy is Si: 5.5-8.0%, Mg: 0.2-0.9%, Cu: 0.1-0.6%, Fe≤0.2%, Mn≤0.4%, Mo≤0.4%, Ni≤0.1%, Sn≤0.1%, Ti≤0.1%, Sr: 0.01-0.02%, and the remainder is Al and unavoidable impurities, wherein the mass ratio of Cu element to Mg element is ≤0.65, the mass ratio of Mn element to Mo element is 1.0-2.0, and the mass ratio of the sum of the mass of Mn element and Mo element to the mass of Fe element is 3.0-6.0. The die-cast aluminum-silicon alloy is prepared by material preparation, smelting, refining, and die-casting, and has excellent tensile strength, yield strength and good plasticity without heat treatment.
[0007] Chinese patent publication number CN114717455B discloses a heat-treatment-free high-strength and toughness die-cast aluminum alloy and its preparation method, the alloy includes: Si 7.5-9.5wt.%, Ni 0-1.5wt.%, Mn0.4-0.8wt.%, Mg 0-0.4wt.%, Cr0.08-0.3wt.%, Zr 0.01-0.15wt.%, Ti0.03-0.11wt.%, Sr 0.005-0.025wt.%, the rest is aluminum and unavoidable impurity elements. The die-cast aluminum alloy of the invention has good thermal stability, and the mechanical properties do not change by more than 10% after being kept at no more than 150°C for 1000h. It has excellent mechanical properties with a die-casting yield strength greater than 120MPa and an elongation greater than 14%. It can meet the performance requirements of the die-cast structural parts of the vehicle body without subsequent heat treatment, and can greatly improve the qualified rate of thin-walled die-cast structural parts and reduce the cost of using automotive parts.
[0008] Chinese patent publication number CN114164362B invents a heat-treatment-free high-strength and toughness aluminum alloy and its forming method. The mass percentage of the aluminum alloy components is Si 8.5-1.5%, Cu 0.05-0.5%, Mg 0.05-0.5%, Mo 0.1-0.5%, Sr 0.005-0.1%, B 0.005-0.1%, Cd 0.05-0.3%, Zr 0.05`-0.25%, and the rest is Al and unavoidable impurities. When forming the aluminum alloy of the present invention, boronization treatment is used to refine the grains, and strontium is used to modify and refine the eutectic silicon. The addition of Mo not only avoids the poisoning phenomenon caused by the simultaneous addition of B and Sr, but also refines the eutectic silicon to a submicron size, greatly improving the strength and toughness of the alloy; at the same time, combined with solid solution strengthening and dispersion strengthening, the alloy is given excellent mechanical properties. The alloy has good fluidity and excellent casting performance, and does not require heat treatment strengthening, saving production processes, reducing production costs, and has a bright application prospect.
[0009] Chinese patent publication number CN105316542B discloses a high-strength and high-toughness die-cast aluminum alloy and its products, which belong to the A1-Si-Mn-Mg-Re system and are composed of the following mass percentages: silicon 7.5-8.5%, manganese 0.3-0.4%, magnesium 0.2-0.3%, rare earth 0.1-0.2%, strontium 0.01-0.02%, iron ≤0.15%, titanium ≤0.10%, copper ≤0.05%, and the rest are aluminum and inevitable trace impurities, wherein the content of a single element of the trace impurities is ≤0.05%, and the total amount of trace impurities is ≤0.15%, and the products are prepared from the above-mentioned high-strength and high-toughness die-cast aluminum alloy. The die-cast aluminum alloy of the invention has high strength and high toughness, and good mechanical properties can be obtained in the cast state without T6 heat treatment. If T6 heat treatment is performed, the mechanical properties of the material will be further improved. This alloy material can meet the development needs of lightweight cars and is used in the manufacture of key components such as car chassis subframes and door pillars.
[0010] The heat treatment-free die-casting alloy disclosed in the above patent ensures the fluidity, strength and toughness of the alloy by adding alloy elements such as Si, Mg, Cu, V, Zr, rare earth and Sr. All alloys are added with 0.01-0.06% Sr (strontium). The addition of Sr makes the aluminum melt particularly easy to absorb air, and it is difficult to ensure the purity of the melt. Even after refining and degassing, the hydrogen content exceeds 0.18ml / 100gAl. In addition, in large-scale industrial production, the aluminum melt stays in the melting furnace for a long time. In the subsequent vacuum die-casting production trial process, due to the high hydrogen content of the melt, there are also a large number of loose holes and defects in different positions of the casting. The porosity is locally higher than the requirement of <5% for general die-casting parts, resulting in large fluctuations in the elongation of the actual trial products, and it is difficult to reach more than 10% in some areas. Summary of the invention
[0011] The purpose of the present invention is to provide a heat-treatment-free die-casting aluminum alloy and a preparation method thereof, so as to solve the problem that the Sr element deterioration of such heat-treatment-free die-casting alloy causes melt inhalation, resulting in unstable elongation, so that the alloy die-casting can obtain a structure without obvious holes and loose defects in various places inside, thereby ensuring that the as-cast tensile strength is greater than 200MPa, the yield strength is greater than 120MPa, and the elongation of various parts of the component is greater than 10%.
[0012] To achieve the above object, the technical solution of the present invention is:
[0013] A heat treatment-free die-casting aluminum alloy comprises the following components by mass percentage: Si 6.5-9.5%, Fe 0.1-0.3%, Mn 0.4-0.85%, Mg 0.1-0.6%, Ti 0.02-0.12%, Sb 0.05-0.15%, and the rest comprises Al and other unavoidable impurity elements; and at the same time satisfies: Fe+Mn≥0.65%, Mn / Fe=2.0-6.6.
[0014] Furthermore, the remainder is Al and other inevitable impurity elements.
[0015] Preferably, the content of a single element in the inevitable impurity elements is ≤0.075%, and the total amount is ≤0.3%. Preferably, the inevitable impurity elements include but are not limited to Cr, V, Ni, Sn or Zn.
[0016] Furthermore, it also includes one or more elements of Sr≤0.01%, Mo≤0.15%, and Zr≤0.15%.
[0017] Preferably, Fe is 0.1-0.15%, and / or Mn is 0.55-0.65%, and / or Mg is 0.1-0.4%, and / or Ti is 0.05-0.1%, and / or Sb is 0.08-0.13%.
[0018] The microstructure of the die-cast aluminum alloy of the present invention is α-Al+(α+Si) eutectic, the eutectic silicon is in the form of round particles, the size of which reaches the submicron level; and there is no coarse needle-shaped iron-containing phase and no obvious loose holes.
[0019] The die-cast aluminum alloy of the present invention has a tensile strength greater than 200 MPa, a yield strength greater than 120 MPa, and an elongation greater than 14%.
[0020] In the composition design of the die-casting aluminum alloy of the present invention:
[0021] The Si element in aluminum alloy can significantly improve the die-casting fluidity of aluminum alloy, and at the same time improve the strength. The higher the silicon content, the more eutectic structure, the better the fluidity, the higher the strength, but the toughness will decrease. The present invention controls the Si element content to 6.5-9.5%, which ensures the fluidity of the alloy, reduces the proportion of eutectic silicon phase, and improves the plasticity of the alloy.
[0022] The maximum solid solubility of Fe in Al is only 0.052%. In deformed aluminum alloys, Fe is generally treated as an impurity. In die-cast aluminum alloys, the demoulding effect of Fe is almost irreplaceable in some cases. At the same time, it improves the high-temperature mechanical properties and thermal cracking resistance of the alloy. However, Fe is easy to form coarse needle-shaped β-Al5FeSi phase in die-cast aluminum alloys, resulting in reduced strength and toughness. For this reason, the present invention controls the Fe content to 0.1-0.3%.
[0023] The Mn element has little effect on the strength of the die-casting alloy, but Mn can transform the β-Al5FeSi phase into a block-shaped or Chinese character-shaped AlFeMnSi phase, thereby improving the toughness of the alloy and improving the die-casting aluminum alloy's sticking performance. Too high Mn elements will form a large-sized manganese-containing phase, affecting the toughness of the alloy. In order to have a good demolding performance of the alloy, the sum of the mass of the Fe element and the Mn element is controlled to be ≥0.65%; in order to improve the morphology of the iron-containing phase, the present invention controls the mass ratio of the Mn element to the Fe element to be 2.0 to 6.6.
[0024] Mg element is added to the die-casting alloy to form Mg2Si phase, which can increase the tensile strength, hardness and corrosion resistance of aluminum alloy die-castings. However, an increase in Mg content will reduce the toughness and fluidity of the alloy, increase the shrinkage and thermal cracking tendency of the alloy, and has a particularly prominent effect on large-sized castings. Therefore, the present invention controls the Mg element content to 0.1-0.6%.
[0025] The Ti element is used to refine the aluminum matrix and is usually added to the alloy together with the B element. During the solidification process, fine TiB2 and Al3Ti phases are preferentially precipitated, which can serve as heterogeneous nucleation points to refine the grains. Excessive Ti elements can easily lead to agglomeration of TiB2 particles, affecting the toughness of the alloy. For this reason, the Ti element content is controlled within a range of 0.02 to 0.12% in the present invention.
[0026] Mo is a more effective Fe neutralizer than Mn, and can transform the β-Al5FeSi phase into a fine α-Al(Mo,Fe)Si phase. Adding Mo together with Mn can completely modify both the pre-eutectic and eutectic β-Fe phases. This phase is evenly dispersed in the aluminum matrix, which can effectively block the movement of dislocations, improve the alloy strength, and enhance toughness. In order to control the alloy cost, the present invention controls the Mo content to ≤0.15%.
[0027] Zr element can generate Al3Zr phase in aluminum alloy, which has similar crystal structure with Al3Ti phase, has low lattice mismatch with α-Al solid solution state, and can also refine grains. In addition, Zr can also generate nano-scale dispersed phase uniformly distributed in the aluminum matrix, which can pin dislocations and improve the strength of cast aluminum alloy at room temperature and high temperature. In order to control the alloy cost, the present invention controls the Zr element content to ≤0.15%.
[0028] The Sr element is widely used in die-cast aluminum alloys for the modification of eutectic silicon, which modifies the coarse and slender eutectic silicon into short fibers, reduces the splitting effect on the matrix, and avoids the reduction of plasticity caused by stress concentration. However, the increase in Sr content will increase the gas absorption of the alloy and increase the gas content in the alloy. In order to control the purity of the alloy melt so as to stably improve the elongation of the casting, the present invention controls the Sr element content to ≤ 0.01%.
[0029] The Sb element can produce AlSb phase in aluminum alloy. This phase precipitates before α-Al in the melt, promoting the nucleation and growth of α-Al. As the Si phase precipitates from the melt, it adheres to the AlSb phase. At the same time, α-Al grows and wraps the Si phase and AlSb phase. Therefore, the Sb element can effectively modify the eutectic silicon, and can effectively change the eutectic silicon from coarse flakes to fine flakes or even round particles. The size of eutectic silicon can reach submicron level, and it can also refine the aluminum matrix, making the dendritic aluminum matrix rods thinner and more uniform. Figure 1 The cast structure of the poorly modified hypoeutectic aluminum-silicon alloy. Figure 2 , Figure 3 It is the cast structure of hypoeutectic aluminum-silicon alloy modified with 0.02% Sr. Figure 4 , Figure 5 It is the cast structure of the hypoeutectic aluminum-silicon alloy modified by 0.1% Sb.
[0030] The melts of the above structures are all processed by the same process and obtained by semi-continuous casting.
[0031] Figure 1 The eutectic silicon inside the middle circle is poorly deteriorated, and the eutectic silicon is in the shape of long strips, with a size of more than 10 microns; Figure 2 , Figure 3 The eutectic silicon modification effect of the alloy with 0.02% Sr content is very good. The eutectic silicon is in the form of dots with a maximum size of about 7 microns, but there are many holes in it with a size of 70 to 140 microns; Figure 4 , Figure 5The eutectic silicon modification effect of the alloy with 0.1% Sb content is equivalent to the former. The eutectic silicon is also distributed in a dotted manner, with a maximum size of about 8 microns, but without holes, only slightly loose, and the loose size is less than 25 microns. The above-mentioned structure is obtained by a semi-continuous casting process, and its cooling rate is much lower than that of die casting. After the die casting process is adopted, the size of eutectic silicon will be further refined to obtain a submicron level. In addition, the Sb addition modification process is simple, the modification effect lasts for a long time, and the remelting of the Sb-modified alloy still maintains a good modification effect. However, too high an Sb element content will produce a flocculent or even coarse needle-shaped AlSb phase, resulting in a sharp decrease in mechanical properties. Therefore, the present invention controls the Sb element content to 0.05-0.15%.
[0032] The present invention also provides a method for preparing the heat treatment-free die-casting aluminum alloy, comprising the following steps:
[0033] 1) Melting the above ingredients to obtain an alloy melt, and controlling the material temperature at 720-730°C;
[0034] 2) adding a sodium-free slag remover to the alloy melt by powder spray refining, wherein the weight of the sodium-free slag remover accounts for 0.1-0.5% of the total weight of the alloy melt, and controlling the material temperature at 720-730° C.; adding a sodium-free covering agent to the alloy melt after slag removal, wherein the weight of the sodium-free covering agent accounts for 0.05-0.1% of the total weight of the alloy melt;
[0035] 3) After degassing the alloy melt with a rotary degasser, control the material temperature at 720-730°C and remove the surface slag; use argon + chlorine mixed gas with an argon flow rate of 3.5-4.5m 3 / h, chlorine gas flow rate 0.05~0.15m 3 / h, degassing time 10-20min; control the hydrogen content in the alloy melt ≤ 0.14ml / 100gAl;
[0036] 4) The alloy melt after refining and degassing is tested for composition and hydrogen content. If the test is qualified,
[0037] The temperature is cooled to 690-720°C to obtain a heat-treatment-free die-cast aluminum alloy.
[0038] Preferably, in step 1), the required aluminum raw material is put into a smelting furnace for melting and heated to 760-790° C.; then silicon, manganese, antimony, molybdenum and zirconium raw materials are added, and after the raw materials are completely melted, the temperature is controlled at 730-750° C., magnesium raw materials are added and stirred, and after the raw materials are completely melted, the temperature is controlled at 720-730° C., titanium and strontium raw materials are added and stirred, and after the raw materials are completely melted, an alloy melt is obtained, and the material temperature is controlled at 720-730° C.;
[0039] Preferably, in the step 2) of powder spraying and refining, argon gas is used as a carrier, and the argon gas flow rate is 0.1-0.3 m 3 / h, refining time is 5 to 10 minutes, the sodium-free slag remover and sodium-free covering agent are powdery, and the particle size is ≤2mm.
[0040] Preferably, the rotor speed of the rotating degasser in step 3) is 400-450 r / min.
[0041] Preferably, the aluminum raw material is pure aluminum or recycled aluminum that meets the alloy composition requirements, the silicon raw material is aluminum-silicon master alloy or industrial silicon or quick-dissolving silicon, the manganese raw material is aluminum-manganese master alloy or manganese agent, the antimony raw material is aluminum-antimony master alloy, the molybdenum raw material is aluminum-molybdenum master alloy, the strontium raw material is aluminum-strontium master alloy, the zirconium raw material is aluminum-zirconium master alloy, the titanium raw material is aluminum-titanium-boron master alloy rod or aluminum-titanium-carbon-boron master alloy rod, and the magnesium raw material is pure magnesium.
[0042] Preferably, the aluminum-silicon master alloy is Al20Si, the aluminum-manganese master alloy is Al10Mn, the aluminum-antimony master alloy is Al10Sb, the aluminum-molybdenum master alloy is Al5Mo, the aluminum-strontium master alloy is Al10Sr, the aluminum-zirconium master alloy is Al10Zr, the aluminum-titanium-boron master alloy is Al5TiB, and the aluminum-titanium-carbon-boron master alloy is Al2Ti0.2C0.2B.
[0043] In the method for preparing the heat treatment-free die-casting aluminum alloy of the present invention:
[0044] Step 3) Rotary degassing, using argon + chlorine mixed gas, argon flow rate 3.5 ~ 4.5m 3 / h, chlorine gas flow rate 0.05~0.15m 3 / h, degassing time 10 ~ 20min, by mixing a small amount of chlorine in the degassing medium argon, using the dispersed argon bubbles to absorb hydrogen in the melt, while using the chlorine to react chemically with hydrogen in the melt, the degassing capacity is improved and the hydrogen content in the melt is controlled to be ≤0.14ml / 100gAl.
[0045] The removal of hydrogen from molten aluminum alloy is through the reaction of hydrogen atoms to generate hydrogen gas and transfer it to the gas phase. The reaction process is controlled by the hydrogen partial pressure difference between the melt and the gas phase. When the hydrogen partial pressure in the melt is higher than that in the gas phase, the melt precipitates hydrogen. Argon gas is introduced into the melt. The hydrogen partial pressure in the argon bubbles is lower than that in the melt. The hydrogen in the melt diffuses into the argon bubbles and generates hydrogen gas, which is carried out of the melt as the argon bubbles float up.
[0046] The degassing rotor rotates at high speed, breaking the argon gas flowing out of the rotor outlet into very small bubbles, increasing the surface area and dispersion of the bubbles in the melt, so that the argon bubbles can more fully contact the hydrogen atoms in the melt, thereby improving the degassing efficiency. The rotor speed determines the bubble crushing and dispersion effect during the degassing process. The higher the rotor speed, the better the bubble crushing and dispersion effect, and the better the degassing effect. Too high a rotation speed will cause the equipment to become unstable and easily cause the rotor to break and fail; too low a rotation speed will cause the bubbles in the melt to be too large, and the range of action will be limited to a very small area around the rotor. The bubbles will float up quickly in the melt, with a short residence time and poor hydrogen capture effect. Therefore, the present invention preferably controls the rotor speed at 400-450r / min.
[0047] The argon flow rate entering the rotor is related to the rotor speed. Too low argon flow rate results in a small number of bubbles in the melt, while too high argon flow rate results in the rotor being unable to fully break up and disperse the bubbles. The excess bubbles cause the small bubbles to re-aggregate into large bubbles, which float near the rotor and cause the liquid surface to churn, resulting in a decrease in degassing efficiency. Therefore, the argon flow rate is controlled at 3.5-4.5m 3 / h.
[0048] Add a small amount of chlorine to the argon gas, and use the reaction of chlorine in the melt to enhance the degassing ability. The main reactions are as follows: Cl2+H2=2HCl↑ and 2Al+3Cl2=2AlCl3↑. Chlorine directly reacts with hydrogen to remove hydrogen. At the same time, AlCl3 and HCl generated by the reaction of chlorine and aluminum float in the melt in gaseous state, which also brings about the adsorption degassing effect. Since chlorine reacts directly with Al, excessive chlorine will cause slag formation in the melt. Therefore, the chlorine flow rate is 0.05~0.15m 3 / h.
[0049] Rotary degassing introduces argon into the melt to absorb hydrogen in the melt. To control the hydrogen content of a large amount of melt at a low level, sufficient degassing time must be ensured. Too short a degassing time will obviously lead to incomplete degassing. When the hydrogen content in the melt continues to decrease and reaches equilibrium, too long a degassing time cannot further reduce the hydrogen content of the melt, but instead causes slag oxidation of the melt. Therefore, the degassing time is controlled at 10 to 20 minutes.
[0050] Compared with the prior art, the advantages of the present invention are:
[0051] 1. In existing alloys, eutectic silicon is generally modified by adding Sr elements. Sr will reduce the liquid filling capacity of the alloy during the solidification process, which is prone to shrinkage and shrinkage defects. To ensure the modification effect of eutectic Si, the amount of Sr added is usually 0.02%. The high Sr content causes serious air absorption in the alloy melt. The existing degassing process in the die-casting industry is difficult to control the hydrogen content of the melt to below 0.18ml / 100gAl, which makes the subsequent vacuum die-casting parts more prone to loose holes. The loose size of some holes can reach more than 100 microns.
[0052] The heat-treatment-free die-cast aluminum alloy of the present invention adds Sb element to replace Sr element for the first time, and performs modification treatment on eutectic silicon, which can effectively avoid the problem of high hydrogen content caused by high Sr content melt absorption. For hypoeutectic Al-Si die-cast aluminum alloy, eutectic silicon in the alloy structure is coarse needle-shaped, which seriously deteriorates the mechanical properties of the alloy.
[0053] 2. The present invention modifies eutectic silicon by adding Sb element, which can effectively change the eutectic silicon from coarse flakes to fine flakes or even round particles, reaching the submicron level (0.1-1μm), and can refine the aluminum matrix, making the dendritic aluminum matrix bars thinner. Compared with the existing method of adding Ti element alone, the composite refining effect is better, and the aluminum matrix dendrites are evenly distributed, thereby significantly improving the mechanical properties, especially the elongation.
[0054] 3. The present invention uses Sb element to modify and refine the alloy, and the process is simple and the modification effect lasts for a long time. Even if the alloy is remelted, it does not need to be treated again and still maintains a good modification effect. However, the modification process of adding Sr element is relatively complicated, because Sr is easy to volatilize in high-temperature melt, the addition yield is low, and Sr element needs to be added again when the alloy is remelted.
[0055] 4. The melt degassing process in the preparation method of the present invention adopts argon-chlorine mixed gas as the degassing medium for the first time in the heat-treatment-free die-casting aluminum alloy, which improves the melt degassing efficiency and ensures that the hydrogen content inside the melt can be controlled below 0.14ml / 100gAl, providing the prerequisite for vacuum die-casting of low-porosity components, thereby steadily improving the elongation of the components. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 It is the cast structure of poorly modified hypoeutectic aluminum-silicon alloy;
[0057] Figure 2 This is a photo of the cast structure of the hypoeutectic Al-Si alloy modified with 0.02% Sr;
[0058] Figure 3 This is a magnified photo of the cast structure of the hypoeutectic Al-Si alloy modified with 0.02% Sr;
[0059] Figure 4 This is a photo of the cast structure of the hypoeutectic Al-Si alloy modified with 0.1% Sb;
[0060] Figure 5 This is a magnified photo of the cast structure of the hypoeutectic Al-Si alloy modified with 0.1% Sb;
[0061] Figure 6 This is a typical metallographic structure photo of the cross section of the vacuum die-casting test piece of Example 5 of the present invention;
[0062] Figure 7 This is an enlarged photo of a typical metallographic structure of a cross section of a vacuum die-casting test piece of Example 5 of the present invention;
[0063] Figure 8 This is a typical metallographic structure photograph of the cross section of the comparative vacuum die-casting specimen. DETAILED DESCRIPTION
[0064] The present invention is further described in detail below in conjunction with the embodiments and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0065] The aluminum alloy composition of the embodiment of the present invention is shown in Table 1, and the remainder of the composition includes Al and other inevitable impurities; the preparation process parameters of the embodiment of the present invention and the comparative example are shown in Table 2. Table 3 shows the performance parameters of the embodiment of the present invention and the comparative example.
[0066] Example 1
[0067] A heat-treatment-free die-casting aluminum alloy, the alloy composition content by weight is: Si 6.5%, Fe 0.22%, Mn 0.45%, Mg 0.38%, Ti 0.08%, Sb 0.15%, the rest is Al and other inevitable impurity elements, the content of a single element in the inevitable impurity elements is ≤0.075%, and the total amount is ≤0.3%; the preparation method thereof comprises:
[0068] (1) preparing pure aluminum, pure Mg, Al20Si, Al10Mn, Al10Sb and Al2Ti0.2C0.2B according to the above alloy weight ratio, and preheating and drying the raw materials to remove moisture;
[0069] (2) Put the required aluminum raw material into a smelting furnace for melting, heat it to 770°C, then add Al20Si, Al10Mn and Al10Sb, and after the raw materials are completely melted, control the temperature at 740°C, add Mg raw material and stir, and after the raw materials are completely melted, control the temperature at 730°C, add Al2Ti0.2C0.2B and stir, and after the raw materials are completely melted, obtain an alloy melt, and control the material temperature at 730°C;
[0070] (3) The alloy melt is subjected to a composition test. After the composition is qualified, a sodium-free slag remover is added to the melt by powder spray refining. The weight of the sodium-free slag remover accounts for 0.2% of the total weight of the alloy melt. The material temperature is controlled at 730°C. After slag removal, a sodium-free covering agent is added to the alloy melt. The weight of the sodium-free covering agent is determined according to the surface size of the melt and accounts for about 0.05% of the total weight of the alloy melt. Powder spray refining uses argon as a carrier with an argon flow rate of 0.1m 3 / h, refining time 10min, sodium-free slag remover and sodium-free covering agent are powdery, with a particle size of ≤2mm;
[0071] (4) After the alloy melt is degassed by a rotary degasser, the material temperature is controlled at 730°C and the surface slag is scraped off; the degassing process is: rotor speed 400r / min, argon + chlorine mixed gas, argon flow rate 3.5m 3 / h, chlorine gas flow rate 0.05m 3 / h, degassing time 10min;
[0072] (5) The alloy melt after refining and degassing is subjected to composition detection and hydrogen content detection. The melt acceptance standard is: the composition is qualified, and the hydrogen content is measured by ABB-Alscan hydrogen meter ≤ 0.14ml / 100gAl; after the test is qualified, it is allowed to stand and cool to 690°C to obtain a heat-treatment-free die-cast aluminum alloy.
[0073] Subsequently, a tensile test bar was prepared by a vacuum die-casting method, with a die-casting temperature of 690°C, a mold temperature of 200°C, an injection speed of 2.5 m / s, a casting pressure of 65 MPa, and a vacuum degree of 200 mbar.
[0074] Comparative Example
[0075] A heat treatment-free die-casting aluminum alloy, the alloy composition mass percentage is: Si 8.01%, Fe 0.12%, Mn 0.56%, Mg 0.35%, Ti 0.11%, Sr 0.025wt.%, the rest is aluminum and inevitable impurity elements, the content of a single element in the inevitable impurity elements is ≤0.075%, and the total amount is ≤0.3%; the preparation method thereof comprises:
[0076] (1) preparing pure aluminum, pure Mg, Al20Si, Al10Mn, Al10Sr and Al2Ti0.2C0.2B according to the above alloy weight ratio, and preheating and drying the raw materials to remove moisture;
[0077] (2) Put the required aluminum raw materials into a smelting furnace for melting, heat to 770°C, then add Al20Si and Al10Mn, after the raw materials are completely melted, control the temperature at 740°C, add Mg raw materials and stir, after the raw materials are completely melted, control the temperature at 730°C, add Al2Ti0.2C0.2B and Al10Sr and stir, after the raw materials are completely melted, obtain an alloy melt, and control the material temperature at 730°C;
[0078] (3) The alloy melt is subjected to a composition test. After the composition is qualified, a sodium-free slag remover is added to the melt by powder spray refining. The weight of the sodium-free slag remover accounts for 0.25% of the total weight of the alloy melt. The material temperature is controlled at 725°C. After slag removal, a sodium-free covering agent is added to the alloy melt. The weight of the sodium-free covering agent is determined according to the size of the melt surface and accounts for about 0.1% of the total weight of the alloy melt. Powder spray refining uses argon as a carrier with an argon flow rate of 0.12m 3 / h, refining time 9.5min, sodium-free slag remover and sodium-free covering agent are powdery, with a particle size of ≤2mm;
[0079] (4) After the alloy melt is degassed by a rotary degasser, the material temperature is controlled at 728°C and the surface slag is scraped off; the degassing process is: rotor speed 425r / min, argon + chlorine mixed gas, argon flow rate 4m 3 / h, chlorine gas flow rate 0.08m 3 / h, degassing time 15min;
[0080] (5) The alloy melt after refining and degassing is subjected to composition testing. After passing the test, the alloy melt is allowed to stand and cool to 695° C. to obtain a heat-treatment-free die-cast aluminum alloy.
[0081] Subsequently, a tensile test bar was prepared by a vacuum die-casting method, with a die-casting temperature of 690°C, a mold temperature of 200°C, an injection speed of 2.5 m / s, a casting pressure of 65 MPa, and a vacuum degree of 200 mbar.
[0082] The mechanical properties of the die-casting test pieces made of the aluminum alloy of the present invention and the mechanical properties of the die-casting test pieces made of the comparative alloy and the size of eutectic silicon are shown in Table 3. The microstructure photos of Example 5 and the comparative example are shown in Figure 6 , Figure 7 and Figure 8 shown.
[0083] Figure 6 , Figure 7 This is a typical optical micrograph of the cross section of the test piece in Example 5. The internal structure of the material is fine and uniform, without coarse needle-shaped iron-containing phases. The eutectic silicon modification effect is good. The eutectic silicon is dot-shaped and the size is less than 1 micron. ImageJ software is used to calculate Figure 7The average size of the eutectic silicon particles is 0.75 microns, reaching the submicron level; and there are no obvious holes inside, only a small amount of looseness, thus ensuring the high elongation of the embodiment.
[0084] Figure 8 This is a typical optical micrograph of the cross section of the comparative test piece. The internal structure of the material is fine and uniform, without coarse needle-shaped iron-containing phases. The eutectic silicon modification effect is also good. The average size of the eutectic silicon particles is 0.81 microns, which can also reach the submicron level; however, there are obvious hole defects, and the size of the aggregation area reaches more than 100 microns, which reduces the elongation of the comparative example.
[0085] As can be seen from Table 3, the tensile strength of the die-cast test piece is greater than 265 MPa, the yield strength is higher than 120 MPa, and the elongation is increased by more than 40% compared with 10%, reaching 14%. Although the strength of the comparative example can also meet the requirements, the elongation is only 8.8%.
[0086] In summary, the present invention adopts Sb element modification / refinement process to achieve good modification effect of eutectic silicon, which can effectively avoid the problem of high hydrogen content caused by high Sr content melt absorption, and cooperates with the rotary degassing process to control the hydrogen content of the alloy to below 0.14ml / 100gAl. After die-casting, the internal structure is fine and uniform, without coarse needle-shaped iron-containing phase, and the eutectic silicon is round and granular. The size can reach submicron level, and there is no obvious loose holes. The excellent mechanical properties of the die-cast yield strength greater than 120MPa and the elongation greater than 14% can be obtained. It is suitable for vacuum die-casting to manufacture large integrated automotive parts, so that the porosity of the parts is less than 5%, and the elongation reaches more than 10%, which meets the subsequent connection requirements.
[0087]
[0088]
[0089]
Claims
1. A heat-treatment-free die-casting aluminum alloy, wherein the components by mass percentage are: Si 6.5-9.5%, Fe 0.1-0.3%, Mn 0.4-0.85%, Mg 0.1-0.6%, Ti 0.02-0.12%, Sb 0.05-0.15%, and the rest include Al and other unavoidable impurity elements; and at the same time satisfy: Fe+Mn≥0.65%, Mn / Fe=2.0-6.
6.
2. The heat treatment-free die-casting aluminum alloy according to claim 1, characterized in that: The rest is Al and other inevitable impurity elements.
3. The heat treatment-free die-casting aluminum alloy according to claim 1 or 2, characterized in that: The content of a single element in the inevitable impurity elements is ≤0.075%, and the total amount is ≤0.3%. Preferably, the inevitable impurity elements include but are not limited to Cr, V, Ni, Sn or Zn.
4. The heat treatment-free die-casting aluminum alloy according to claim 1, 2 or 3, characterized in that: It also includes one or more elements of Sr≤0.01%, Mo≤0.15%, and Zr≤0.15%.
5. The heat treatment-free die-casting aluminum alloy according to claim 1, 2, 3 or 4, characterized in that: Fe 0.1-0.15%, and / or Mn 0.55-0.65%, and / or Mg 0.1-0.4%, and / or Ti 0.05-0.1%, and / or Sb 0.08-0.13%.
6. The heat treatment-free die-casting aluminum alloy according to claim 1, 2, 3, 4 or 5, characterized in that: The microstructure of the die-cast aluminum alloy is α-Al+(α+Si) eutectic, the eutectic silicon is in the form of round particles, the size of which reaches the submicron level, and there is no coarse needle-shaped iron-containing phase and no obvious loose holes.
7. The heat treatment-free die-casting aluminum alloy according to claim 1, 2, 3, 4, 5 or 6, characterized in that: The die-cast aluminum alloy has a tensile strength greater than 265 MPa, a yield strength greater than 120 MPa, and an elongation greater than 14%.
8. A method for preparing a heat-treatment-free die-casting aluminum alloy as claimed in any one of claims 1 to 7, characterized in that: The steps include: 1) Smelting the components according to claim 1, 2, 3, 4 or 5 to obtain an alloy melt, and controlling the material temperature at 720-730°C; 2) adding a sodium-free slag remover to the alloy melt by powder spray refining, wherein the weight of the sodium-free slag remover accounts for 0.1-0.5% of the total weight of the alloy melt, and controlling the material temperature at 720-730° C.; adding a sodium-free covering agent to the alloy melt after slag removal, wherein the weight of the sodium-free covering agent accounts for 0.05-0.1% of the total weight of the alloy melt; 3) After degassing the alloy melt with a rotary degasser, control the material temperature at 720-730°C and remove the surface slag; use argon + chlorine mixed gas with an argon flow rate of 3.5-4.5m 3 / h, chlorine gas flow rate 0.05~0.15m 3 / h, degassing time 10-20min; control the hydrogen content in the alloy melt ≤ 0.14ml / 100gAl; 4) The alloy melt after refining and degassing is tested for composition and hydrogen content. After passing the test, it is allowed to stand and cool to 690-720° C. to obtain a heat-treatment-free die-cast aluminum alloy.
9. The preparation method according to claim 8, characterized in that: Step 1) Put the required aluminum raw material into a smelting furnace for melting and heat to 760-790°C; then add silicon, manganese, antimony, molybdenum, and zirconium raw materials, and after the raw materials are completely melted, control the temperature at 730-750°C, add magnesium raw material and stir, and after the raw materials are completely melted, control the temperature at 720-730°C, add titanium and strontium raw materials and stir, and after the raw materials are completely melted, obtain an alloy melt, and control the material temperature at 720-730°C.
10. The preparation method according to claim 8, characterized in that: In the step 2) of powder spraying and refining, argon gas is used as a carrier, and the argon gas flow rate is 0.1-0.3 m 3 / h, refining time is 5 to 10 minutes, the sodium-free slag remover and sodium-free covering agent are powdery, and the particle size is ≤2mm.
11. The preparation method according to claim 8, characterized in that: In step 3), the rotor speed of the rotating degasser is 400-450 r / min.
12. The preparation method according to claim 8 or 9, characterized in that: In step 1), the aluminum raw material is pure aluminum or recycled aluminum that meets the alloy composition requirements, the silicon raw material is aluminum-silicon master alloy or industrial silicon or quick-soluble silicon, the manganese raw material is aluminum-manganese master alloy or manganese agent, the antimony raw material is aluminum-antimony master alloy, the molybdenum raw material is aluminum-molybdenum master alloy, the strontium raw material is aluminum-strontium master alloy, the zirconium raw material is aluminum-zirconium master alloy, the titanium raw material is aluminum-titanium-boron master alloy rod or aluminum-titanium-carbon-boron master alloy rod, and the magnesium raw material is pure magnesium.
13. The preparation method according to claim 12, characterized in that: The aluminum-silicon master alloy is Al20Si, the aluminum-manganese master alloy is Al10Mn, the aluminum-antimony master alloy is Al10Sb, the aluminum-molybdenum master alloy is Al5Mo, the aluminum-strontium master alloy is Al10Sr, the aluminum-zirconium master alloy is Al10Zr, the aluminum-titanium-boron master alloy is Al5TiB, and the aluminum-titanium-carbon-boron master alloy is Al2Ti0.2C0.2B.
Citation Information
Patent Citations
A high-strength, high-toughness die-cast aluminum alloy and its products
CN105316542B
A heat-tough aluminum alloy without heat treatment and its forming method
CN114164362B
A heat-treasure-free high-strength and high-toughness die-cast aluminum alloy and its preparation method
CN114717455B
Heat-treatment-free aluminum alloy material and forming process thereof
CN115505795A
Cited By
Al-Si-Mg series aluminum alloy and preparation method and application thereof
CN121575277A